Peran Bank Sampah RW 8 Kelurahan Gunung Anyar Tambak Surabaya dalam Pengelolaan Sampah untuk Pelestarian Lingkungan - M. Hilmy Febriansyah; Cundaningsih, Nurvita (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Waste management in Indonesia remains a significant challenge with implications for health and the environment. This research uses descriptive quantitative methods, including observation and interviews, to analyse the role of Bank Sampah RW 8 Gunung Anyar Tambak, Surabaya, in community-based waste management. From 2020 to 2024, the number of waste banks increased from one to three, and they succeeded in reducing the generation of inorganic waste by 84,358 kg, a reduction of 8,456 kg, or 10.02%. The number of waste bank members also increased by 39.89%, from 140 to 351 people. The waste exchange rate system enables residents to save valuable waste, which is then converted into cash, thereby providing a tangible economic benefit. Although the programme contributes only 0.0063% to Surabaya City's total waste reduction, it promotes environmental awareness and the circular economy at a local level. In conclusion, waste banks are effective in reducing household waste while improving community welfare.